2000
DOI: 10.1161/01.str.31.12.3067
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Testing for Coagulopathies in Patients With Ischemic Stroke

Abstract: Background-Hypercoagulable states are a recognized, albeit uncommon, etiology of ischemic stroke. It is unclear how often the results of specialized coagulation tests affect management. Using data compiled from a systematic review of available studies, we employed quantitative methodology to assess the diagnostic yield of coagulation tests for identification of coagulopathies in ischemic stroke patients. Summary of Review-We performed a MEDLINE search to identify controlled studies published during 1966 -1999 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
4
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(90 citation statements)
references
References 99 publications
3
72
4
11
Order By: Relevance
“…59 Therefore, laboratory tests for coagulopathy may be reserved in selected patients. In clinical practice, a much more important cause of coagulapathy is cancer.…”
Section: Workup For Cancer-related Coagulopathymentioning
confidence: 99%
“…59 Therefore, laboratory tests for coagulopathy may be reserved in selected patients. In clinical practice, a much more important cause of coagulapathy is cancer.…”
Section: Workup For Cancer-related Coagulopathymentioning
confidence: 99%
“…All are inherited through autosomal-dominant transmission and all have been associated with an increased risk of VTE; however, none has convincingly been demonstrated to be risk factors for arterial thrombosis. [1][2][3] Homozygosity for these defects significantly enhances the risk of thrombosis; however, homozygotes are rare and the bulk of the data presented here comes from heterozygotes.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune disease also may induce a prothrombotic state promoting stroke, such as an HIV patient with protein C and protein S deficiency who developed a stroke in the presence of a PFO [15]. The prevalence rates of anti-cardiolipin antibodies in patients with ischemic strokes were 17-21% [16]. A retrospective case series of 40 patients showed that anti-phospholipid antibodies and hypercoagulability is common in patients with PFO [17].…”
Section: Resultsmentioning
confidence: 99%